The Variability of Crossbreed-cashew Accession Numbers at Two Years Age Based on Morphological Characters - Wawan Haryudin; Otih Rostiana; Jajat Darajat (Buletin Penelitian Tanaman Rempah dan Obat, 2018)
Cashew in cross-pollinated plants, one effort to improve the diversity gentik in germplasm of cashew nut was carried out by a cross between high-producing elders  and the elderly tolerant of helopeltis sp. The aimed of this study is to know the variability of 25 accession of cashew nut hybrid based on leaf morphology characters. The study was conducted at Cikampek Experimental Station, from January to December 2016, using direct observation method  the qualitative and quantitative morphological characters of the cashew at the age of two years. Observations were done on eight plants per plot, each observed as many as 50 leaves per plant. The result showed that the morphology character of cashew nut varied. Character of leaf ovatus, obovatus, and oblong The trunk and rounded ends, pointed and blunt. Form the edge of the leaf, form the bottom and top surfaces smooth leaves. The color of the adult leaves was dark green, and young leaves were reddish brown and  yellowish  green.  The  diversity  18.35-100 %  and  the level the closeness of 0.10-0.38, divided into two groups. Group one separated by characters a leaf shape  oblongus,  leaf  base  form  of the rotundatus, leaf tip shape rotundatus and obtusus and young leaves color BGB N199 A, group two separated by the characters of the leaf shape obovate, leaf base form of the obtusus, leaf tip shape acuminatus and retusus and young leaves color GB 200 B. The lenght of the leaf characters, the width of the leaf, the leaf thickness and the length of the petiole vary with the degree of diversity 47.67-96.94 % and the proximity distance 0.19-6.19 which is divided into teo groups. One group was separated by the the highest leaf length character 17.6-20.6 cm, whereas the two group was separated by the smallest leaf length character 14.6-17.1 cm.